Crude Oil-Induced Reproductive Disorders in Male Goldfish: Testicular Histopathology, Sex Steroid Hormones, and Sperm Swimming Kinematics - Mahlouji, Mahboubeh; Alavi, Sayyed Mohammad Hadi; Ghasemi, Jahanbakhsh; Jalili, Amir Hossein; Mozanzadeh, Mansour Torfi; Zhang, Songpei; Shazada, Nururshopa Eskander; Butts, Ian A E; Hoseinifar, Seyed Hossein; Linhart, Otomar (Journal of applied toxicology, 2025)
Crude oil contamination has been shown to impair reproduction in aquatic animals through carcinogenic and genotoxic properties. Here, we assessed the endocrine-disrupting function of crude oil on male reproductive system based on testicular histology, sex steroid hormones, and fertility endpoints in adult male goldfish (Carassius auratus), which were exposed to 0.02- to 2-mg/L crude oil for 21 days (Experiment #1) or to 5- to 250-mg/L crude oil for 9 days (Experiment #2). The crude oil contained 0.22-mg/L nickel (Ni), 1.10-mg/L vanadium (V), and 12.87-mg/L polycyclic aromatic hydrocarbons (PAHs). Twenty-four hours after adding crude oil, the sum of PAHs ranged from 0.30 to 2.28 μg/L in the aquaria containing 0.02- and 250-mg/L crude oil, respectively. Water analyses for heavy metals in Experiment #2 showed high concentrations (mg/L) of Ni (0.07-0-09) and V (0.10-0.21). For both experiments, exposure to crude oil did not impact gonadosomatic index; however, testes showed histopathological defects including hyperplasia or hypertrophy of Sertoli cells, depletion of the Leydig cells, necrosis of germ cells, and fibrosis of lobular wall. In Experiment #1, sperm production and motility, testosterone (T), and 17β-estradiol (E2) were not significantly different among treatments. In Experiment #2, the number of spermiating males decreased by ~50% following exposure to 250-mg/L crude oil. Sperm production, motility kinematics, T, and the T/E2 ratio significantly decreased in males exposed to ≥ 50-mg/L crude oil; however, E2 remained unchanged. Results show crude oil-induced imbalance of sex steroid hormones disrupts spermatogenesis resulting in diminished sperm production and motility.
Keywords: testis; sperm quality; Water Pollutants, Chemical; ropa; Endocrine Disruptors; zvířata; polycyclic aromatic hydrocarbons; Goldfish; Spermatozoa; Sperm Motility; testosterone; mužské pohlaví; heavy metals; 17β‐estradiol; motilita spermií; pohlavní steroidní hormony; Reproduction; rozmnožování; Testis; Gonadal Steroid Hormones; Animals; chemické látky znečišťující vodu; karas zlatý; spermie; Male; Petroleum; endokrinní disruptory